2011
DOI: 10.1080/13607863.2010.536138
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health and memory self-efficacy as mediators in the relation between subjective age and life satisfaction among older adults

Abstract: This study fills a gap in existing literature and suggests that a youthful subjective age is associated with higher life satisfaction because it is related to higher evaluation of health and memory self-efficacy. It provides an initial support for a resource-based explanation of the relation between subjective age and life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
97
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 58 publications
17
97
1
1
Order By: Relevance
“…Recent developments on the scientific study of adjustment to aging (AtA), conceptualized it, according to identity process theory, as involving the three processes of identity assimilation (maintaining self-consistency), identity accommodation (making changes in the self), and identity balance (maintaining a sense of self but changing when necessary) (Sneed & Whitbourne, 2003) whereas according to Moreover, how old a person feels, designates subjective age (SA) (Barak, 2009;Barrett, 2005;Kleinspehn-Ammerlahn, Kotter-Grühn & Smith, 2008;Montepare, 2009). In addition, SA was found to contribute to subjective health, memory self-efficacy, and life satisfaction, regardless of the chronological age (Stephan, Caudroit & Chalabaev, 2011), which is consistent with studies showing that older individuals' own evaluation of their age is a better predictor of psychological functioning than an objective count of chronological years (Montepare, 2009;Schafer & Shippee, 2010).…”
Section: Introductionsupporting
confidence: 73%
“…Recent developments on the scientific study of adjustment to aging (AtA), conceptualized it, according to identity process theory, as involving the three processes of identity assimilation (maintaining self-consistency), identity accommodation (making changes in the self), and identity balance (maintaining a sense of self but changing when necessary) (Sneed & Whitbourne, 2003) whereas according to Moreover, how old a person feels, designates subjective age (SA) (Barak, 2009;Barrett, 2005;Kleinspehn-Ammerlahn, Kotter-Grühn & Smith, 2008;Montepare, 2009). In addition, SA was found to contribute to subjective health, memory self-efficacy, and life satisfaction, regardless of the chronological age (Stephan, Caudroit & Chalabaev, 2011), which is consistent with studies showing that older individuals' own evaluation of their age is a better predictor of psychological functioning than an objective count of chronological years (Montepare, 2009;Schafer & Shippee, 2010).…”
Section: Introductionsupporting
confidence: 73%
“…Prior research has found a positive relationship between a younger subjective age and memory self-efficacy (the belief in the effectiveness of one's memory function, 18,22 which contributes to the maintenance of memory performance with advancing age 23 ). Health and lifestyle patterns are another argument in favor of a subjective ageecognition relationship.…”
Section: E14mentioning
confidence: 99%
“…15 There is an increasing discrepancy between subjective age and chronological age as people grow older, and the majority of older adults feel younger than they actually are despite age-related changes. 15e17 Subjective age predicts important outcomes, including well-being, 18 physical functioning, 19 self-rated health, 18 and longevity. 20 In most of these studies, a younger subjective age contributes to more favorable psychological and health-related outcomes, independent of chronological age, and beyond other demographic factors (e.g., education, sex, marital status) and health variables (e.g., disease burden).…”
Section: E14mentioning
confidence: 99%
“…Internalization of age stereotypes about memory as applying to oneself [19,20] may affect subjective memory. Younger subjective age is known to be associated with higher memory self-efficacy [21] and fewer memory complaints [7] in older adults.…”
Section: Introductionmentioning
confidence: 99%